Screening Teucrium polium for glucose lowering activity in a rat model - Ireng, Anita (Curtin University, 2012)
The glucose lowering effects of the herb Teucrium polium for treating Type II diabetes mellitus was investigated. The methanolic extract of the plant was assessed acutely in an animal model against metformin, insulin and vehicle. The current study indicates that the extract can significantly (p<0.01) reduce blood glucose levels in vivo.